Prevalence and Antimicrobial Resistance of Bacterial Pathogens in Diabetic Foot Infections: A Clinical Microbiological Study - Raziq, Abdul; Zahoor, Muhammad Mohsin; Mannan, Abdul; Usman, Saqib (Journal of Neonatal Surgery, 2025)
Background: Diabetic foot infections (DFIs) are a major complication of diabetes mellitus, frequently associated with antimicrobial resistance and poor clinical outcomes. Objective: To determine the prevalence of bacterial pathogens in diabetic foot infections and assess their antimicrobial susceptibility patterns. Methodology: This cross-sectional study was conducted at the Medical Unit of Northwest General Hospital and Research Center, Peshawar, from December 2019 to June 2020. A total of 140 adult diabetic patients aged 20–70 years with clinically diagnosed DFIs were included. Specimens were collected from ulcers, processed using standard bacteriological techniques, and antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method according to CLSI guidelines. Data were analyzed with SPSS version 22.0. Results: The mean age of patients was 60.4 ± 7.8 years, with 70.71% males and 29.29% females. The most frequent ulcer grade was Wagner grade 2 (45.00%). Escherichia coli was the most prevalent isolate (53.57%), followed by Staphylococcus aureus (21.43%), Klebsiella species (18.57%), and Streptococcus species (6.43%). Pathogen distribution varied with age and ulcer severity, with Klebsiella significantly higher in older patients (23.53% vs. 5.26%, p=0.013) and Streptococcus species more common in grade 3 ulcers (11.63%, p=0.000). Patients with a history of toe or foot amputation showed a higher prevalence of Klebsiella (22.77% vs. 7.69%, p=0.039). Antimicrobial susceptibility revealed high resistance among Gram-negative organisms to cephalosporins, whereas carbapenems demonstrated comparatively better activity. Conclusion: Escherichia coli was the predominant pathogen in DFIs, and high resistance to commonly used antibiotics highlights the need for ongoing surveillance and rational antibiotic prescribing.